Effective oxygenated boron groups of boron-doped photoreduced graphene oxide for photocatalytic removal of volatile organic compounds - Tai, Xin Hong; Lai, Chin Wei; Yang, Thomas Chung Kuang; Chen, Chia Yun; Abdullah, Abdul Halim; Lee, Kian Mun; Juan, Joon Ching (Elsevier, 2022)
The adverse health effects from indoor air pollutants such as volatile organic compounds (VOCs) has intrigued much attention. Photocatalytic oxidation (PCO) is a promising technique to degrade VOCs under ambient conditions. A metal-free photocatalyst, namely boron-doped photoreduced graphene oxide (BPRGO) was synthesized via a facile, scalable, and cost-effective UV irradiation method. The BPRGO photocatalyst managed to remove 80% of the VOCs (100 mg/m3 of methanol) within 6 h (0.283 h−1) under UV-A irradiation. Moreover, up to 91% of the VOCs were successfully mineralised into harmless CO2. The high photoactivity of BPRGO-1.0 was due to the high amount of oxygenated boron groups (OBGs) namely BC2O and BCO2 groups. The suitable amount of B dopants led to a higher hole carrier density and p-type conductivity. This had retarded the charge carrier recombination which improved the photocatalytic removal of VOCs. This work provides new insights of metal-free BPRGO photocatalyst for VOCs removal.